AB0545 Interferon Alpha2a versus Cyclosporin A for The Treatment of Severe Ocular Behcet's Disease – A Prospective, Randomised, Single Blind, National Multicenter Trial (INCYTOB). (15th July 2016) - Kötter, I.; Vonthein, R.; Schoenfisch, B.; Xenitidis, T.; Doycheva, D.; Henes, J.; Stübiger, N.; Feist, E.; Heiligenhaus, A.; Rath, T.; Max, R.; Mackensen, F.; et al.
Abstract : Background: Behcet`s disease (BD) is a variable vessel vasculitis. To date, there are only retrospective case series showing efficacy of interferon alpha for ocular BD. This trial was started in 2007. Objectives: To prove that interferon alpha2a is at least as effective as cyclosporin A. Methods: Maintenance dosage of IFN was 3 to 9 Mill iU 3x/week, CSA dosage 3 to 5 mg/kg, adapted to response every two weeks. In case of nonresponse, the patients were switched to the alternative treatment arm after week six. Efficacy was measured by Posterior Uveitis scoring system (PUS), Behcet`s disease current activity form (BDCAF), Health assessment questionnaire (HAQ) and Beck depression Inventory (BDI) were also used. Primary endpoints were time to remission by PUS and number of cross over from one arm to the other. Results: The study was stopped in 2013 after 37 patients due to slow recruitment. 13 patients per treatment arm (n=26, 65% male, 35% female, 38% German, 50% Turkish, 12% other, mean age 30.5 years) were evaluated. All 13 patients with primarily IFN achieved remission of their ocular disease, 9 of 13 in the CSA arm (p=0.096). The median time to complete PUS remission was 84 vs. 72 days, p=0.899. The probability to achieve remission after one year was 0.92 for IFN (95% CI 0.49–0.99) and 0.62 for CSA (95%CI 0.24–0.81). There were significantly more switches from CSA to IFN (n=7) than vice versa (n=1) (p=0.030). The main reasons were inefficacy (n=4 for CSA) and/or side effects (n=3 for CSA). PUS of the affected eyes improved significantly in both arms during the first year (p<0.001). Visual acuity at baseline was significantly better in the CSA arm than in the IFN arm, hence a significant improvement over time could only be shown in the IFN arm (p<0.003 week 30). BDCAF improved in both arms (p>0.001), as did HAQ (p=0.047). Safety analysis revealed more hair loss (p=0.004) and cytopenia (p<0.001) in the IFN and hypertension (p=0.048) in the CSA arm. Conclusions: Both treatments are effective for ocular and extraocular BD. There is a tendency towards superiority of interferon alpha considering that there were more switches from CSA to IFN due to inefficacy and side effects. Due to the small sample size, this did not reach significance. A prospective international multicenter trial may help to overcome these limitations. Acknowledgement: This trial was supported by the German Ministry of Health (BMBF/DLR, No. 01KG0706) and by Roche (supply of interferon alpha2a) Disclosure of Interest: None declared